The assassination of Martin Luther King Jr - Stein, R. Conrad (New York Children's Press/Grolier Pub, 1996)
Chronicles the events leading up to, and the immediate aftermath of, the murder of one of the best-known figures in the United States civil rights movement
Hurg
5
Keywords: African Americans -- Biography; Civil rights workers